NO reduction under diesel exhaust conditions over Au/Al2O3 prepared by deposition-precipitation method - Miguel, P.; Granger, P.; Jagtap, Neelam; Shubhangi B. Umbarkar; Dongare, Mohan K.; Dujardin, Christophe (Journal of Molecular Catalysis A-Chemical, 2010)
Gold supported on alumina was prepared by urea deposition-precipitation method and compared to silver supported on alumina for the selective catalytic reduction of NO by hydrocarbons under lean conditions. The catalyst showed activity in the reduction of NO and 100% selectivity towards N-2 in the temperature range 300-350 degrees C. At higher temperature the NO conversion decreased due to competitive oxidative reactions of the reductants. XPS analysis confirmed the good stability of gold nanoparticles deposited on alumina. Infrared studies showed the formation of various adsorbed species (formates, carboxylates, ad-NOx and cyanide) on the catalyst surface. Addition of H-2 to the feed containing decane enhanced the formation of these species on the catalyst surface as well as the catalytic activity for the NO conversion to N-2. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Deposition-precipitation; Gold; In situ IR; NO reduction; XPS